Efektivitas Teknik In House Training Sebagai Upaya Meningkatkan Kompetensi Guru - Nurhabibi, Nurhabibi (JURNAL GLOBAL EDUKASI, 2020)
Abstract: The implementation of this classroom action research departs from the background of the need for renewal in teaching and learning activities both carried out by teachers and by students, especially those aimed at finding out the effectiveness of In House Training Techniques as an Effort to Improve Teacher Competence in Preparing RPP and Teaching and Learning Activities at SDN 016501 Pulo Bandring Kec. Pulo Bandring TP. 2019/2020; The school action research was conducted at SDN 016501 Pulo Bandring. The subjects of this study were teachers of SDN 016501 Pulo Bandring, data were collected through observation, interviews, tests, and study documentation. Through training activities scientifically proven to improve teacher competence in compiling syllabus and lesson plans at SDN 016501 Pulo Bandring Kec. Pulo Bandring. This is evidenced by the increase in the number of good teacher syllabi from 31% to 83% after academic supervision. In addition, the number of good quality RPPs also increased from 31% to 89%. Keywords: In House Training; teacher competence, teaching and learning activities  Abstrak: Dilaksanakannya penelitian tindakan kelas ini berangkat dari latar belakang perlunya pembaruan dalam kegiatan belajar mengajar baik yang dilakukan oleh guru maupun oleh siswa khususnya yang bertujuan untuk mengetahui efektivitas Tehnik In House Training Sebagai Upaya Meningkatkan Kompetensi Guru Dalam Menyusun RPP dan Kegiatan Belajar Mengajar di SDN 016501 Pulo Bandring Kec. Pulo Bandring TP. 2019/2020; Penelitian tindakan sekolah dilaksanakan di SDN 016501 Pulo Bandring. Subjek penelitian ini adalah guru SDN 016501 Pulo Bandring, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Melalui Kegiatan Pelatihan terbukti secara ilmiah dapat meningkatkan kompetensi guru dalam menyusun silabus dan RPP di SDN 016501 Pulo Bandring Kec. Pulo Bandring. Ini terbukti dengan meningkatnya jumlah silabus guru yang baik dari 31% menjadi 83% setelah supervise akademik. Selain itu jumlah RPP yang berkualitas baik juga meningkat dari 31% menjadi 89%. Kata Kunci: In House Training; Kompetensi Guru, kegiatan belajar mengajar